Mediational role of metabolic syndrome between physical activity, sedentary behavior and non-alcoholic fatty liver disease: a cross-sectional study - Zhaoyu Ren; Hongxuan Fan; Yaya Xue; Xinyu Yang; Xuchang Liu; Jing Luo; Jianqi Zhao; Leigang Wang; Yao Zhang; Bin Liang (BMC Public Health)
Abstract Background Physical activity (PA), sedentary behavior (SB), metabolic syndrome (MetS), and non-alcoholic fatty liver disease (NAFLD) have been linked in previous studies. Nevertheless, it is unclear whether MetS has a mediating influence on the relationships among physical activity, sedentary behavior, and non-alcoholic fatty liver disease. This study aims to assess the connections between physical activity, sedentary behavior, and non-alcoholic fatty liver disease and to explore the extent to which metabolic syndrome acts as a mediator in this association. Methods A total of 3351 adults from the National Health and Nutrition Examination Survey (NHANES) from 2017 to 2018 were included in our study. Physical activity and sedentary behavior were categorized as work activity (WA), recreational activity (RA), walking/bicycling (for commuting) and sedentary behavior to investigate the association with metabolic syndrome and non-alcoholic fatty liver disease. Besides, mediation analysis was utilized to determine the extent to which metabolic syndrome mediates the relationships among inadequate physical activity, prolonged sedentary behavior, and non-alcoholic fatty liver disease. Results Regression analysis revealed that a reduced risk of developing NAFLD was associated with sufficient recreational activity (OR = 0.61, 95% CI: 0.44–0.83, P = 0.004), while an increased risk of MetS was observed in sedentary behavior group (OR = 1.28, 95% CI: 1.00–1.64, P < 0.05). In addition, strong associations were detected between MetS and NAFLD. Mediation analysis indicated that metabolic syndrome accounts for 17.9% of the influence that recreational activity has on the risk of NAFLD. Subgroup analysis indicated sex differences in these associations. Specifically, recreational activity may not significantly influence the risk of developing NAFLD in females, and the mediating role of MetS was no longer significant in both sex-specific subgroups. Conclusion In the general adult population, metabolic syndrome may account for nearly 18% of the association between insufficient recreational activity and non-alcoholic fatty liver disease.